Adequacy of the Global Financial Safety Net-Review of the Flexible Credit Line and Precautionary and Liquidity Line, and Proposals for Toolkit Reform. (Policy Papers; Policy Paper ;, 2017)
protracted global uncertainty combined with frequent episodes of capital flow volatility have intensified demand for liquidity support. In response to calls from the IMFC and the G20, the Fund has identified gaps in the global financial safety net (GFSN) and the Fund's lending toolkit for crisis prevention, including insufficient coverage against liquidity pressures resulting from volatile capital flows. The proposals in this paper draw on the previous Fund work on the adequacy of the GFSN, the review of the Fund's current toolkit for crisis prevention, and extensive consultations with the membership. The review of the FCL concludes that the FCL has been effective in providing precautionary support against external tail risks. Successor FCL arrangements and associated access levels have been in line with the assessment of external risks and potential balance of payments needs. However, there is scope to strengthen the transparency and predictability of the qualification framework by adding indicator-based thresholds to complement and inform judgment. To enhance crisis resilience while improving the Fund's toolkit coherence and resource use, the paper proposes three complementary reforms: The establishment of a Short-term Liquidity Swap to provide renewable and reliable liquidity support against potential short-term moderate volatility of capital flows. The proposed instrument is for members with very strong fundamentals and economic policies, and tailored to improve reliability and appeal to users. The use of a core set of indicators with thresholds to guide judgment in FCL qualification. This will improve predictability and transparency while keeping the standards unchanged. The elimination of the PLL to maintain a streamlined and coherent toolkit, given the low use of the PLL, likely reflecting issues of tiering with the FCL. The paper also discusses possible reforms of the current commitment fee policy to promote a more balanced use of Fund resources. Possible options include increasing the commitment fee at high access levels or introducing a new time-based commitment fee.